The importance of crop residues in the diet of Fulani cattle in the sub-humid zone. A preliminary investigation - Kurmin Biri, Katchia, Kaduna state - Nigeria - Kaufmann, Ralph R. von; Magaji, S.O.; Leeuw, P.N. de (International Livestock Centre for Africa, 1978)
Presents results of a preliminary investigation carried out in Nigeria, to determine the contribution of crop residues to the diet of cattle owned by settled Fulani on Katchia Grazing Reserve; to assess the yield of millet & sorghum residues, and to examine the relationship between farmers and livestock owners w. regard to the use of residues.